2000
DOI: 10.1037/0022-0167.47.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, separation, and women's vocational development: A longitudinal analysis.

Abstract: This study tested a proposed model investigating the relations among attachment to and separation from parents, career self-efficacy, and career aspiration over a 5-year period with a sample of 207 young women. Results suggested that being attached to parents may lead to the development of confidence in pursuing career-related tasks, which in turn influences career aspiration. Separation from parents did not have direct effects on career self-efficacy. Results also indicated that women's career plans changed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
119
2
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(139 citation statements)
references
References 56 publications
10
119
2
4
Order By: Relevance
“…There is empirical support that an array of factors influence women's career choices that that have considerably less predictive power for men, including self-efficacy, consideration of the needs of others (Betz, 1994), and attachment to parents (O'Brien, Friedman, Tipton, & Linn, 2000). The literature suggests that support from a range of sources, including teachers and advisors, is particularly instrumental in women's choice of nontraditional majors in STEM fields.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There is empirical support that an array of factors influence women's career choices that that have considerably less predictive power for men, including self-efficacy, consideration of the needs of others (Betz, 1994), and attachment to parents (O'Brien, Friedman, Tipton, & Linn, 2000). The literature suggests that support from a range of sources, including teachers and advisors, is particularly instrumental in women's choice of nontraditional majors in STEM fields.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Young women are more likely than young men to consult others about career decisions and are more influenced by the opinions of others (Seymour & Hewitt, 1997) and often consider the needs of others when making career decisions (Betz, 1994;Cook, 1993;O'Brien et al, 2000). The…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study that supported this line of reasoning, less than 1% of the 207 young women studied indicated that career pursuits were more important than family pursuits (O'Brien, Friedman, Tipton and Linn, 2000). Furthermore, there is still the perception that parenting is a female role and directly affects a woman's choice to become a professor (Van Anders 2004).…”
Section: Female Participation In Stemmentioning
confidence: 99%
“…There is a rich and diverse literature to find alternative answers to this question. Within the career literature, researchers have studied the family influence on career development (Young, Friesen, & Pearson, 1988), career selection (Bratcher, 1982), career exploration (Blustein, 1997), development of vocational interests (Turner & Lapan, 2002), development of vocational values (Lapan, Hinkelman, Adams, & Turner, 1999), career expectations (Paa & McWhirter, 2000), career orientation (O'Brien, Friedman, Tipton, & Linn, 2000). To some extent, all of these issues are related with career decision-making process.…”
Section: Introductionmentioning
confidence: 99%